Teachers’ Readiness and Challenges in Local Wisdom-based Science Learning through Interactive Pop-Up Book Media in Elementary Schools - Sumadi, Conny Dian; Setyawan, Agung (Widyagogik, 2025)
This study aims to explore elementary school teachers’ readiness and challenges in implementing local wisdom-based science learning through interactive pop-up book media. Contextual science learning that integrates local culture requires adequate teacher readiness in pedagogical competence, professional skills, and instructional media development. This research employed a qualitative descriptive approach. The participants were elementary school teachers in Madura, Indonesia. Data were collected through in-depth interviews, classroom observations, and document analysis. Data analysis followed the Miles and Huberman model, consisting of data reduction, data display, and conclusion drawing and verification. The findings reveal that most teachers possess conceptual awareness of the importance of integrating local wisdom into science learning; however, their practical readiness remains limited. Major challenges include insufficient skills in developing instructional media, limited time, lack of hands-on professional training, and inadequate institutional support. Interactive pop-up book media is perceived as highly potential to support local wisdom-based science learning, yet its implementation requires continuous teacher professional development and supportive school policies. This study recommends systematic capacity-building programs to enhance teachers’ competencies in developing and implementing innovative, culturally responsive science learning media.